2014
DOI: 10.1001/jama.2014.7859
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Phenytoin-Related Severe Cutaneous Adverse Reactions

Abstract: This study identified CYP2C variants, including CYP2C9*3, known to reduce drug clearance, as important genetic factors associated with phenytoin-related severe cutaneous adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
3
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(194 citation statements)
references
References 44 publications
9
165
3
9
Order By: Relevance
“…Further analysis demonstrated that phenytoin induced severe cutaneous reactions are strongly associated with carriage of the CYP2C9*3 allele (overall OR 11, 95% CI, 6.2-18; p<0.00001; OR for SJS/TEN in subgroup analysis = 30). 82 Phenytoin is metabolized to an inactive metabolite by the CYP2C9 enzyme and variation in this gene was associated with a 93-95% reduction in drug clearance in the study population. Additionally, delayed phenytoin clearance was observed in patients with phenytoin-ADR in the absence of CYP2C9 variants suggesting that other factors contribute to phenytoin accumulation.…”
Section: Drug-specific Models: Abacavirmentioning
confidence: 92%
See 2 more Smart Citations
“…Further analysis demonstrated that phenytoin induced severe cutaneous reactions are strongly associated with carriage of the CYP2C9*3 allele (overall OR 11, 95% CI, 6.2-18; p<0.00001; OR for SJS/TEN in subgroup analysis = 30). 82 Phenytoin is metabolized to an inactive metabolite by the CYP2C9 enzyme and variation in this gene was associated with a 93-95% reduction in drug clearance in the study population. Additionally, delayed phenytoin clearance was observed in patients with phenytoin-ADR in the absence of CYP2C9 variants suggesting that other factors contribute to phenytoin accumulation.…”
Section: Drug-specific Models: Abacavirmentioning
confidence: 92%
“…In a subgroup analysis, the OR for HLA-B*15:02 carriage as a predictor of phenytoin-SJS/TEN was found to be 5.0 (p=0.25) and this association has been observed in prior studies. 66,[82][83][84] Combined screening for CYP2C9 variants and HLA-B*15:02 carriage improved the sensitivity for phenytoin-SJS/TEN to 62.5% but decreased the specificity (to 86.2% from 97.7% for CYP2C9 variant alone) of the screening strategy. 82 These findings add to a growing number of observations showing that multiple processes including pharmacological and immunological mechanisms contribute to ADRs that may be mediated by the parent drug, and that dose dependency is likely a key feature of both on-target and off-target ADRs ( Figure 1).…”
Section: Drug-specific Models: Abacavirmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, HLA-A*3101 has also been associated with an even broader range of carbamazepine hypersensitivity reactions, including mild maculopapular exanthema, hypersensitivity syndrome and SJS/TEN in European populations [149]. Very recently, CYP2C variants, including CYP2C9*3, known to reduce drug clearance, have been related to phenytoin-related severe cutaneous adverse reactions in populations from Japan and Malaysia [150].…”
Section: Epilepsymentioning
confidence: 99%
“…Several investigations informed about the effect of genetic polymorphisms of CYP2C9/19 on the pharmacokinetics of PHT [27,28]. The metabolism capacity of PHT is clearly impaired in subjects with mutations in CYP2C9/19 genes (poor metabolizers) and so could be the detoxification of the arene oxide and the metabolism of p-HPPH.…”
Section: Influence Of the Pht Dosage Regimementioning
confidence: 99%